Inventory of Pollution Sources for The Lakes of Universiti Tun Hussein Onn Malaysia - Hamdan, Rafidah; Md Ali, Zarina; Azman, Muhammad Hafiq Afifi; Siddiqui, Zuhaib (International Journal of Integrated Engineering, 2024)
Eutrophication impacts freshwater systems worldwide. Eutrophication may occur naturally, although human-caused causes are common. Human activities that release phosphorus and nitrogen cause anthropogenic eutrophication, which increases organic matter production. Lake eutrophication affects surface water globally. Water pollution may be assessed through point sources (PS) and non-point sources (NPS). PS is the intentional or inadvertent release of pollutants from industrial and wastewater facilities into waterways. PS is simpler to control than NPS due to rules and monitoring. Agriculture, urban development, and natural processes in the lake's watershed may cause NPS pollution. Many causes cause NPS contamination, including precipitation, air deposition, infiltration, drainage, and watershed water flow variations. The pollution inventory activity has been carried out in several selected lakes at UTHM, specifically Tasik Kemajuan (in front of the G3 building), Tasik Teknologi (in front of Fakulti Kejuruteraan Awam dan Alam Bina, FKAAB), Tasik Teknologi (in front of Fakulti Pendidikan Teknikal dan Vokasional, FPTV), and Tasik Pembangunan (in front of Perpustakaan Tunku Tun Aminah, PTTA). Point and non-point pollution sources in the study's area have been evaluated via a site investigation. The water discharge sources and considered pollutants entering the lake were analysed. The UTHM water flow plan is being studied for lake inflow sources. The PS pollutant inventory indicated that cafeteria wastewater and commercial building and faculty drainage systems pollute all lakes. Tasik Teknologi (FPTV) identified palm oil plantation water outflow as a pollutant source that can increase lake nutrient content. In all lakes studied, leaves, grass clippings, and other garden trash reached the water. Tasik Kemajuan, Tasik Teknologi (FKAAB), and Tasik Teknologi (FPTV) received water discharge from other lakes, transporting pollutants. This pollutant's source assessment found most NPS from surface runoff. Road runoff contains several pollutants. Soil, leaves, and organic detritus are natural, while construction materials, exhausted particles, roadside waste, and fertilisers are manmade. Storm drains or surface runoff can carry these pollutants from roads to waterways. Residential and commercial stormwater runoff can transport fertiliser from lawns, gardens, and other well-maintained areas. Rainwater washes fertilisers into storm drains and lakes. Runoff can pollute streams and cause algae blooms. In conclusion, all pollutant sources that contributed to the eutrophication for Tasik Kemajuan, Tasik Teknologi (FKAAB), Tasik Teknologi (FPTV) and Tasik Pembangunan has been identified by conducting the pollutants sources inventory.